Increasing School-Age Children's Understanding of The Impact of Gadgets Through Snake-Ladder Games - Rizqi Nursasmita (International Journal of Community Services, 2023)
Background: Gadgets are one of common technological developments that are usedby all groups,including children. School-age children (6-12 years) use gadgets due toparents who are busy working and gadget prices are getting cheaper due tocompetition in the market.Objective: Reducing the negative impact of gadgets on children, especially schoolstudents.Method: One of the things that can be done is through educational game tools,namely playing snake-ladder games about the negative effects of gadgets. Result: The results obtained are that children's knowledge about the negative effects ofgadgets increases and it is expected to reduce the use of gadgets for school children. Conclusion: This activity was that the results of children's knowledge about thenegative effects of gadgets increased. Furthermore, it can be applied in other HealthCenter Services assisted areas by involving other audio-visual media.